1998
DOI: 10.1518/001872098779591331
|View full text |Cite
|
Sign up to set email alerts
|

Aurally and Visually Guided Visual Search in a Virtual Environment

Abstract: We investigated the time participants took to perform a visual search task for targets outside the visual field of view using a helmet-mounted display. We also measured the effectiveness of visual and auditory cues to target location. The auditory stimuli used to cue location were noise bursts previously recorded from the ear canals of the participants and were either presented briefly at the beginning of a trial or continually updated to compensate for head movements. The visual cue was a dynamic arrow that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…However, although much research has been devoted to the study of spatial presence and presence using psychometrical [2][3][4][5][6][7][8] or psychophysiological methods, [9][10][11][12] only a few studies have focused on the neurophysiological and neuroanatomical underpinnings of spatial presence. Most studies in the neuroimaging domain have used VR stimuli to study cortical activations associated with spatial navigation and spatial processing.…”
Section: Introduction Smentioning
confidence: 99%
“…However, although much research has been devoted to the study of spatial presence and presence using psychometrical [2][3][4][5][6][7][8] or psychophysiological methods, [9][10][11][12] only a few studies have focused on the neurophysiological and neuroanatomical underpinnings of spatial presence. Most studies in the neuroimaging domain have used VR stimuli to study cortical activations associated with spatial navigation and spatial processing.…”
Section: Introduction Smentioning
confidence: 99%
“…Many researchers have investigated the utility of three-dimensional (3D) auditory displays for reducing the workload associated with an overloaded visual channel and for enhancing the detection and identification of visual targets (Flanagan, McAnally, Martin, Meehan, & Oldfield, 1998;Nelson et al, 1998;Perrott, Cisneros, McKinley, & D'Angelo, 1996). Advances in digital signal-processing technology and the development of electromagnetic position trackers have enabled the construction of small, relatively inexpensive spatial audio displays that can be used to aid in visual target acquisition in aircraft cockpits, ground combat vehicles, and training simulators.…”
Section: Introductionmentioning
confidence: 99%
“…There has been extensive research into the effects of stage 1 automation (attention guidance) in target detection tasks. Basic research has reliably demonstrated the capacity for visual cues to reduce search times in target search tasks (see, e.g., Egeth & Yantis, 1997;Flanagan et al, 1998). Applied research has also demonstrated these benefits in military situations , Yeh & Wickens, 2001, helicopter hazard detection (Davison & Wickens, 2001), and a number of other domains (Mosier et al, 1998).…”
Section: Automated Systems and Their Impact On Performancementioning
confidence: 99%